SIFAT VENIR DAN KAYU LAPIS 8 JENIS KAYU DARI SULAWESI TENGAH - M I Jslrandar; Suwandi Kliwon; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1990)
A muly  reault on• the suitability  of 8 wood 1peciesfrom Central Sulawesia  raw  material-for veneeri and plywood  iB re~rted   in ~hiB paper. 1'ae •tudy cons!ited of log peeling characteristic, veneerpropgty 'and  tome phy~cal/mechanical AU  of  ita.  lo,. Tram wood  speciu  could  be peeled in cold c0ndition, producing 0.9 mm and 1.6  mm veneer at propertitia  of plywood  (tripl•     and multiplaa cuffln6 angle between 910  -   92080'.                      •                                                       -                                                                            .7'le average111rinkage of  veneer iB   6.27%,  with  a minimum of 4.98'fo  (Nyatoh) and maximum of 8.14%  (Palapi). Veneer •welling from oven_-dry  to aiNlry  condition  varied between 2.lB'fo   (Nyatoh) and 8.60%  (Durian) with an avera.e-    2.81'-'.                                                                                             '7'1, bondi!JI atrerwth of _p_'f¥_~~     fro_~-~   woo4_•!!1!'*-• (76_'fo)  ti>ntOrms with the Indonaian ttandard for  type IIor ""*" rniatant,  6 wood specia  (62,6'fo) with Japanue standard and 4 specia  (60!1>) with German 1tandard•a:Peciflc •fnJvlty   of  multiplex  ;.  higher than triplex.  Some. mechanical propertie• of multiple% are higher than